Chemical Constitution and Antimicrobial Activity of Kefir Fermented Beverage - Abdul-Raouf Al-Mohammadi; Rehab A. Ibrahim; Ahmed H. Moustafa; Ahmed A. Ismaiel; Azza Abou Zeid; Gamal Enan (Molecules, 2021)
Kefir beverage (KB) is a fermented milk initiated by kefir grains rich with starter probiotics. The KB produced in this study seemed to contain many chemical compounds elucidated by gas chromatography–mass spectrometry (GC-MS) and IR spectra. These compounds could be classified into different chemical groups such as alcohols, phenols, esters, fatty esters, unsaturated fatty esters, steroids, polyalkenes, heterocyclic compounds and aromatic aldehydes. Both KB and neutralized kefir beverage (NKB) inhibited some pathogenic bacteria including Escherichia coli ATCC11229 (E. coli), Listeria monocytogenes ATCC 4957 (L. monocytogenes), Bacillus cereus ATCC 14579 (B. cereus), Salmonella typhimurium ATCC 14028 (Sal. typhimurium) as well as some tested fungal strains such as Aspergillus flavus ATCC 16872 (A. flavus) and Aspergillus niger ATCC 20611 (A. niger), but the inhibitory activity of KB was more powerful than that obtained by NKB. It also appeared to contain four lactic acid bacteria species, one acetic acid bacterium and two yeast species. Finally, the KB inhibited distinctively both S. aureus and Sal. typhimurium bacteria in a brain heart infusion broth and in some Egyptian fruit juices, including those made with apples, guava, strawberries and tomatoes.